Developing A Live Worksheet For Hortatory Exposition Writing Instruction in Senior High School - Suci Samiarti; Sri Supiah Cahyati; Yana (PROJECT (Professional Journal of English Education), 2026)
This study aimed to develop and evaluate a Live Worksheet-based instructional material for teaching Hortatory Exposition Text writing, examine its validity and feasibility through expert validation and student responses, and identify students' responses toward the developed product. Employing Borg and Gall's Research and Development model, the study involved 73 eleventh-grade students at a senior high school in West Bandung Regency, selected through purposive sampling across preliminary (n=20) and main field testing (n=53) phases. Data were collected through a 10-item Likert-scale questionnaire covering four thematic areas: worksheet attractiveness, ease of use, writing benefits, and general student response, alongside a six-aspect observation checklist, analyzed quantitatively using feasibility percentage criteria. The developed worksheet incorporated interactive features including fill-in-the-blank, drag and drop, arrow-matching, multiple choice, and microphone-based activities with automated feedback, structured around a four-stage writing plan guiding students from brainstorming through drafting, peer review, and final text revision. Expert validation yielded an overall mean of 3.69 (92.4%, Very Feasible), while student responses produced a combined mean of 3.12 and feasibility percentage of 78.0%, categorized as Feasible, with students reporting improved writing confidence, idea development, and structural understanding of Hortatory Exposition Text. These findings confirm that the developed Live Worksheet is a valid, feasible, and engaging instructional medium for supporting Hortatory Exposition Text writing instruction at the senior high school level.